Design of the Turntable Structure and the FEM Analysis of the Shipborne/Vehicleborne Radar - Yan Xiufeng; Zhou Xiaowei; Zhang Chenghao (Jixie chuandong)
The structure design of the shipborne / vehicleborne project is carried out,through the describing of the turntable design requirements,the whole physical structure style and characteristics are introduced.Meanwhile,considering the practical working conditions of the turntable,the impact and random vibration are simulated by using the FEA method. Then,by comparing the simulation result with the material performance of the turntable,it shows that the turntable structure design meets the requirement.